A screening for canine distemper virus, canine adenovirus and carnivore protoparvoviruses in Arctic foxes (Vulpes lagopus) and red foxes (Vulpes vulpes) from Arctic and sub-Arctic regions of Norway - Tryland, Morten; Balboni, Andrea; Killengreen, Siw Turid; Mørk, Torill; Nielsen, Ole; Yoccoz, Nigel Gilles; Anker Ims, Rolf; Fuglei, Eva (Norwegian Polar Institute, 2018)
Canine distemper virus (CDV), canine adenovirus (CAdV) and canine parvovirus type 2 (CPV-2) cause disease in dogs ( Canis familiaris ). These, or closely related viruses, may also infect wild carnivores. The aim of this study was to investigate exposure to CDV, CAdV and CPV-2 among fox populations in Norway. Arctic foxes ( n = 178) from High-Arctic Svalbard were investigated for antibodies against CDV. Arctic foxes (n = 301) from Svalbard and red foxes from Low-Arctic ( n = 326) and sub-Arctic ( n = 74) regions in Finnmark County, Norway, were investigated for antibodies against CAdV and for the presence of carnivore protoparvovirus DNA in spleen and mesenteric lymph nodes using polymerase chain reaction. Seroprevalence against CDV in Arctic foxes decreased from 25% (1995/96) to 6% (2001/02), whereas the seroprevalence against CAdV increased from 25–40% during the seasons 1995/96 to 2001/02 to 68% for the last study year (2002/03). In red foxes, the seroprevalence against CAdV varied between 31% and 67% for the seasons 2004/05 to 2007/08, increasing to 80% for the last study year. Carnivore protoparvovirus DNA was not detected in any of the 301 Arctic foxes and the 265 red foxes investigated. These results show that CDV and CAdV are enzootic in the Arctic fox population (Svalbard), and that CAdV is enzootic in both the Low-Arctic and sub-Arctic red fox populations (Finnmark). Further studies are needed to better understand the infection biology and the impact of CDV and CAdV in these fox populations, and if viruses may be shared between foxes and other carnivores, including dogs.